Contested essential concepts - Felix Berenskoetter; Stefano Guzzini (Danish Institute for International Studies (DIIS), 2024)
This Working Paper explores the notion of 'essential concepts' and their contestation with an eye on the field of International Relations (IR). The title plays on W.B. Gallie's famous essay to pursue the argument that a debate over the meaning of an essential concept has analytical, normative and political value. The Working Paper is structured around three questions: what are concepts? What makes a concept essential? How should we think about contestation? Starting from the position that concepts play a central role in knowledge production and are embedded in (meta-)theoretical logics that shape their meaning, it discusses how contestation plays out in three domains: abstract and normative theoretical knowledge; explanatory and empirical knowledge; and practical knowledge. The chapter concludes with the argument that meaningful contestation requires translation.
Keywords: 330; concepts; theories; meaning; contestation; translation